A Hominin Femur with Archaic Affinities from the Late Pleistocene of Southwest China. - Darren Curnoe; Xueping Ji; Wu Liu; Zhende Bao; Paul S C Taçon; Liang Ren (PLoS ONE)
The number of Late Pleistocene hominin species and the timing of their extinction are issues receiving renewed attention following genomic evidence for interbreeding between the ancestors of some living humans and archaic taxa. Yet, major gaps in the fossil record and uncertainties surrounding the age of key fossils have meant that these questions remain poorly understood. Here we describe and compare a highly unusual femur from Late Pleistocene sediments at Maludong (Yunnan), Southwest China, recovered along with cranial remains that exhibit a mixture of anatomically modern human and archaic traits. Our studies show that the Maludong femur has affinities to archaic hominins, especially Lower Pleistocene femora. However, the scarcity of later Middle and Late Pleistocene archaic remains in East Asia makes an assessment of systematically relevant character states difficult, warranting caution in assigning the specimen to a species at this time. The Maludong fossil probably samples an archaic population that survived until around 14,000 years ago in the biogeographically complex region of Southwest China.